Treatment of severe symptomatic hyponatremia - Srijan Tandukar; Helbert Rondon‐Berrios (Physiological Reports, 2019)
Abstract Hyponatremia is the most common electrolyte abnormality seen in the hospital. Severe symptomatic hyponatremia is associated with grave consequences including cerebral edema, brain herniation, seizures, obtundation, coma, and respiratory arrest. However, rapid correction of chronic severe hyponatremia may lead to osmotic demyelination syndrome (ODS) and even death. Given the serious consequences of severe hyponatremia or its inadvertent overcorrection, it is of paramount importance for the clinician to be aware of the various scenarios in which hyponatremic patients can present and tailor the management strategies accordingly. We present here a case of severe hyponatremia of unknown duration with the presenting plasma sodium level of 95 mmol/L and use it to illustrate the various treatment strategies – proactive, reactive, or rescue therapy – along with the physiological basis to support these approaches.